Sistem Pendukung Keputusan Pemilihan Guru Terbaik TK Santo Andreas Menggunakan Metode SAW - Sandy Rivaldiansyah; Sri Lestari (E-Jurnal Universitas Samudra, 2022)
In the selection of the best teachers at TK Santo Andreas Jakarta there are still several obstacles, such as the assessment of each teacher is still done manually, namely the principal must fill out the assessment instrument form for each teacher that has been provided, which causes the assessment process to be less accurate and inefficient. In addition, to obtain or find out information on the results of the selection of the best teachers takes quite a long time, because the administrative section must re-enter the value of each teacher into Microsoft Excel and make pranking teacher scores manually. Data collection methods used are interviews, observation and literature study. The decision-making method used by the author is SAW, while the system development method used is the SDLC method with UML design tools. Implementation of the program using the PHP programming language with MySQL database. Decision support systems can be used to facilitate the school in managing data, presenting information, generating reports and reducing errors in calculating grades and getting accurate teacher ranking results and the application of the SAW method can improve the quality of decision making in selecting the best teachers. Based on the results of research conducted at the Santo Andreas Kindergarten, Jakarta, the best teacher scores according to the ranking, namely teacher Theresia Luan with a value of 1.00.